Effect of intermittent preventive treatment during pregnancy with sulfadoxine-pyrimethamine on maternal gestational weight gain in low-income and middle-income countries: A systematic review and individual participant data meta-analysis of randomised clinical trials - Liu, Enju; Partap, Uttara; Shinde, Sachin; Wang, Dongqing; Costa, Janaína Calu; Cliffer, Ilana R.; Wang, Molin; Nookala, Sudeer Kumar; Subramoney, Vishak; Briggs, Brittany; Hamer, Davidson H.; Akurut, Hellen; et al. (Elsevier, 2025)
Background Studies have consistently demonstrated beneficial effects of intermittent preventive treatment during pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) on reducing malaria infection and improving birth outcomes among pregnant women in endemic areas. However, data on its impact on maternal gestational weight gain (GWG) are very limited. We aimed to conduct a two-stage meta-analysis of individual participant data to examine the effect of IPT with SP on GWG compared to other antimalarial regimens.